Critical thinking - Wright, Larry (Oxford University Press, 2001)
Extensively classroom-tested, Critical Thinking: An Introduction to Analytical Reading and Reasoning provides a non-technical vocabulary and analytic apparatus that guide students in identifying and articulating the central patterns found in reasoning and in expository writing more generally...